Public toilets from the perspective of users: a case study in a public place, Brazil. (11th December 2021) - Moreira, Fernanda Deister; Rezende, Sonaly; Passos, Fabiana
Abstract: Public toilets are essential infrastructure to guarantee the right to sanitation in public spaces and, in more general terms, the right to inclusive and sustainable cities. Moreover, since the equipment has a direct user interface, it is important to understand their demands and needs. Given this, the present research aims to understand the perspective of public toilet users on the Pampulha Lake Shore (PLS), a public touristic place in Belo Horizonte, Brazil. For that, observations and semi-structured interviews were carried out with different public toilet users. In addition, comments posted on the Google Local Guides tool of Google Maps were used as a secondary database for understanding users' experience of PLS toilets. The analysis made it possible to identify aspects related to availability, quality (health and hygiene), security, and accessibility. Collected data showed how the conflicting choice of whether or not to use the toilet was directly related to the health and conservation of the urban equipment and interfered with social and leisure prospects. On the whole, the importance of the user's perspective was highlighted in this study with emphasis on elaborating adequate urban planning with regard to health, sanitation, and accessibility issues. HIGHLIGHTS: Public toilets are essential to guarantee the right to sanitation in cities. Users' experience was found crucial for implementing effective public equipments. The case study was used to link users' experience and human rights to sanitation. Availability, accessibility, and quality/safety were the main concerns of users. Google Local Guides was shown as a useful tool to complement users' opinions.